Cryptic radiation within the tadpole-carrying guardian frogs from Borneo, Limnonectes palavanensis and L. finchi (Anura: Dicroglossidae), with the description of eight new species. - J. Maximilian, Dehling; Dario N., Neokleous; Indraneil, Das; T. Ulmar, Grafe; Min, Pui Yong; Stefan T., Hertwig (Magnolia Press, 2025)
we assess genetic, morphological, bioacoustic, and ecological variation within two nominal taxa of tadpole-carrying frogs, the Smooth guardian Frog (Limnonectes palavanensis) from Borneo and Palawan and the rough guardian Frog (L. finchi) from Borneo. The nominal taxon L. palavanensis has been considered to have a wide geographic range on the islands of Palawan and Borneo, both located on Sundaland. Our integrative approach on variation reveals significant differences not only between the populations from Palawan and Borneo but also between sites on Borneo. we designate a lectotype of Limnonectes palavanensis, present a redescription and restrict the range of the nominal species to Palawan Island in the Philippines. we present multiple lines of evidence to demonstrate that the Bornean populations, hitherto assigned to L. palavanensis, in fact represent multiple distinct and evolutionary independent lineages and describe seven new species: Limnonectes gunungensis sp. nov., L. kinabaluensis sp. nov., L. nephophilus sp. nov., L. oreibates sp. nov., L. phylax sp. nov., L. sarawakensis sp. nov., and L. suboliferus sp. nov. we found that the nominal taxon L. finchi consists of two deeply divergent genetic lineages that exhibit consistent corresponding differences in morphology and ecology. we describe the unnamed lineage as a new species, L. gyrinophorus sp. nov. The 10 species within the L. palavanensis group and the L. finchi group can be distinguished by quantitative morphometrics (discriminant analysis, success rate: 91.2% among adult males, 90.3% among adult females) and several qualitative morphological characters, as well as by pairwise genetic divergence of 4.4–18.6% in a segment of the mitochondrial 16S rrNA gene. with few exceptions, the lineage members show allopatric distributions, separated in altitudinal and geographical space. Five of the eight species of the L. palavanensis group from which bioacoustic data are available are distinguished by properties of their advertisement calls. we provide the first analysis of advertisement call properties of L. finchi.